2018
DOI: 10.1371/journal.pone.0207373
|View full text |Cite
|
Sign up to set email alerts
|

Association of gastric and duodenal ulcers with anthropometry and nutrients: Korean National Health and Nutrition Examination Survey (KNHANES II-IV) 2001-2009

Abstract: ObjectivesThe objective of this study was to examine the association of peptic ulcer disease (PUD), including gastric ulcer and duodenal ulcer, with obesity-related indices, nutrients, and blood parameters in Korean adults.MethodsData were obtained from the Second-Fourth Korean National Health and Nutrition Examination Survey (KNHANES II-IV). Binary logistic regression was carried out to analyze the association between PUD and all variables in the crude analysis; in a subsequent analysis, adjustments were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…The association between PUD and obesity was investigated in several studies but the findings remained controversial [4,5,6,7,8,9]. Several studies have reported obesity as an independent risk factor of PUD [4,5,6,7,8]. However, some of these studies had diagnostic limitations, based on self-reported questionnaire for diagnosing PUD [4,6,8].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between PUD and obesity was investigated in several studies but the findings remained controversial [4,5,6,7,8,9]. Several studies have reported obesity as an independent risk factor of PUD [4,5,6,7,8]. However, some of these studies had diagnostic limitations, based on self-reported questionnaire for diagnosing PUD [4,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported obesity as an independent risk factor of PUD [4,5,6,7,8]. However, some of these studies had diagnostic limitations, based on self-reported questionnaire for diagnosing PUD [4,6,8]. Thus, less severe cases of PUD could have been excluded, since they have a lesser chance of visits to doctors to undergo EGD or surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations